Upaya Meningkatkan Hasil Belajar IPS Terpadu Materi Pokok Perubahan Sosial Budaya dan Globalisasi Melalui Penerapan Metode Reciprocal Teaching Siswa Kelas IX.2 MTsN 10 Bireuen - Zahiati A. Bakar (Ranah Research : Journal of Multidisciplinary Research and Development, 2020)
This study aims to see whether learning with reciprocal teaching methods can improve learning outcomes and increase student activity in participating in teaching and learning activities in Integrated Social Studies subjects in grade IX.2 MTsN 10 Bireuen Odd Semester Academic Year 2019/2020. The subjects in this study were 32 students of grade IX.2 MTsN 10 Bireuen. The data in this study was processed by tabulating data and analyzed and processed manually. From the results of the initial data to cycle III, the average learning outcome was 74.91 with completeness reaching 62.50% in cycle I, an average of 83.31 with completeness of 81.25% in cycle II, and an average of 87.78 with completeness reaching 100% in cycle III. The result of this study is that the reciprocal teaching method can improve the learning outcomes of Integrated Social Studies, and increase the competence of the preparation of the Integrated Social Studies cycle in grade IX.2 students, and can increase student activity in participating in teaching and learning activities.